2015
DOI: 10.3109/13625187.2015.1111325
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ information to patients and prescription of the emergency contraceptive pill according to their personal experience of using the method and perception of its mechanism of action

Abstract: The misconception that emergency contraception could cause a mini-abortion was associated with its denial to potential users, while physicians' personal experience of needing to use it favoured the likelihood of their informing potential users about it and prescribing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Finally, Faundes et al’s analysis of a national survey of Brazilian obstetrician-gynecologists found that physicians who had personal experience with the emergency contraceptive pill (among women physicians or the partners of male physicians) reported greater willingness to provide information about the emergency contraceptive pill and to prescribe it. They 24 also found that those physicians who had experienced an unwanted pregnancy and had had an abortion, either themselves or with their partner, reported greater willingness to help a woman obtain an abortion if she requested one. 25…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Faundes et al’s analysis of a national survey of Brazilian obstetrician-gynecologists found that physicians who had personal experience with the emergency contraceptive pill (among women physicians or the partners of male physicians) reported greater willingness to provide information about the emergency contraceptive pill and to prescribe it. They 24 also found that those physicians who had experienced an unwanted pregnancy and had had an abortion, either themselves or with their partner, reported greater willingness to help a woman obtain an abortion if she requested one. 25…”
Section: Discussionmentioning
confidence: 99%
“…One-fifth of the gynecologists interviewed in a Brazilian study had misconceptions about the mechanism of action of LNG. 28 Even though 76.2% of the physicians studied here care for adolescents in their offices, most of them felt uncomfortable prescribing EC. The number of adolescents seen per month was associated with discomfort with EC prescription in the random forest model.…”
Section: Discussionmentioning
confidence: 87%
“…One-fifth of the gynecologists interviewed in a Brazilian study had misconceptions about the mechanism of action of LNG. 28 …”
Section: Discussionmentioning
confidence: 99%
“…19,23,32,[40][41][42][43][44]53,54,64,66,67,69,74,[76][77][78] Several mixed methods studies used quantitative measures to assess provider behavior and incorporated qualitative methods to describe behavioral determinants influencing provider behaviors. 46,59 Among the few studies where associations between behavioral determinants and provider behavior were assessed, the majority considered predisposing factors such as knowledge and attitudes related to specific methods (e.g., emergency contraception and no-scalpel vasectomy), 24,51,79 services (e.g., postabortion care and referral for high-risk clients), 60,73 or clients' attributes 61 and their association with service provision. Only 2 studies considered reinforcing and enabling factors and their association with provider behaviors, specifically quality of care and provider performance.…”
Section: Is the Measurement Theory Driven?mentioning
confidence: 99%